Curcumin-loaded milk-derived sEVs fused with platelet membrane attenuate endothelial senescence and promote spinal cord injury recovery in diabetic mice - Yaozhi He; Siyuan Zou; Jiawei Wang; Wenbin Zhang; Sheng Lu; Mengxian Jia; Yumin Wu; Xiaowu Lin; Ziwei Fan; Qishun Liang; Yizhe Sheng; Qichuan Zhuge; et al. (Materials Today Bio)
Spinal cord injury (SCI) causes devastating neurological deficits, and cellular senescence critically contributes to the pathogenesis of various diseases. Notably, endothelial cells (ECs) senescence exerts a pivotal effect on the pathogenesis following SCI. In this study, we found that the number of senescent ECs increased by 18.87% ± 5.91%, and the disruption of the blood-spinal cord barrier (BSCB) was aggravated with an 18% increase in Evans Blue dye extravasation in diabetic mice with spinal cord injury (DM-SCI). To address this pathological process, a bioinspired nanotherapeutic platform utilizing milk-derived small extracellular vesicles with platelet membrane fusion (PM-sEVs) was developed for the targeted delivery of curcumin (Cur). In vitro, PM-sEVs-Cur effectively mitigated HG/IL-1β-induced HUVECs senescence by 54.19% ± 5.39% and increased expression of the tight junction protein ZO-1 by 4.33-fold. Mechanistically, Cur attenuated HUVECs senescence by activating the NRF2/HO-1 pathway. In vivo, platelet membrane modification enhanced the lesion targeting of sEVs. Treatment with PM-sEVs-Cur attenuated ECs senescence by 34.96% ± 6.59%, preserved BSCB integrity with a 17% reduction in Evans Blue dye extravasation, promoted axonal regeneration with a 6.36-fold increase in neurofilament expression, and improved motor function recovery with an increase of 2.4 ± 0.55 points in Basso Mouse Scale score in DM-SCI. This study highlights PM-sEVs-Cur as a promising therapeutic delivery platform for DM-SCI treatment.